Crossing boundaries : the dislocations of Filipina domestic workers in Thailand - Sarausad, Mary Rose Geraldine; Resurreccion, Bernadette P.; Kusakabe, Kyoko; Zimmermann, Willi; Japanese Government (Pathum Thani, Thailand : Asian Institute of Technology, 2003)
The forced dispersal of Filipinos to different parts of the world (estimated to be around 150 countries) signifies the intensity of the negative economic and employment conditions in the Philippines, prompting the Philippine government to institutionalize the export of unskilled and skilled labor to Asia, United States, Arab States and Europe; thus, providing a solution to a growing internal problem of unemployment, shortage of foreign reserves, high inflation, high national debt, making migrant workers so important to sustain its economy, and providing also a solution to those at the receiving end (the richer countries) who are in short of unskilled and semi-skilled labour supply as a result of changing economic conditions, giving rise to the increasing need for foreign domestic workers or caregivers from the poorer nations such as the Philippines; thus, the internationalization of reproductive labour. Although the feminization of migrant labour is well known, little has been said about the experiences of these women migrants, particularly the domestic workers, in the process of migration. In highlighting the experiences of the domestic helpers in this study, I am able to analyze the dynamics of change in the women's lives in terms of power relations, their roles and position in the household. It is my intention, in the study of their dislocations, to bring out the different underlying factors that intensified these feelings of pain from the perspectives of the Filipina domestic workers themselves, and how gender, other than class and ethnicity, has contributed in creating contradictory effects in their lives.
Thesis (M.Sc.) - Asian Institute of Technology, 2003
A thesis submitted in partial fulfillment of the requirements for the degree of Masters of Science, School of Environment, Resources and Development
Keywords: Domestics -- Thailand; Women domestics -- Thailand